Socio-Philosophical Foundations of Youth Employment and The Implementation of The “Decent Work” Concept in The Context of The Digital Economy - Kurbanov Xurshidbek Pozilovich (Researchparks Publishing, 2026)
The article discusses theoretical and practical questions of employment of young people and the concept of “decent work” in the digital economy. It presents analysis of how digital transformation affects the labour market, with a particular focus on the impact on youth employment, using OECD, ILO, World Bank and the Statistics Agency of the Republic of Uzbekistan data. The study also shows how the digital economy generates new jobs but also presents its difficulties, like skills mismatch, lack of social protection systems adaptability, and digital inequality.